Usure et rupture - Breaking points - Claudine Raynaud, Peter Vernon (dir.) (Presses universitaires François-Rabelais, 1995)
Certain recurrent ideas emerge through the rich diversity of papers collected here under the title Usure et Rupture: the necessity of cultural memory in finding an idiom, the rupture of form to provide a new text which makes sense of the past from the viewpoint of the present, the ways in which the image of usury plays an ambiguous role-both fructifying and economizing the text. A translator's delight, rupture in English can be variously rendered by break up, breaking up, parting, severance, ...